A Contested Crisis: Policy Narratives and Empirical Evidence on Border Deaths in the Mediterranean. (June 2018) - Steinhilper, Elias; Gruijters, Rob J
Death and suffering of migrants at Europe's Mediterranean Sea border has become one of the defining moral and political issues of our time. While humanitarian organizations argue that deaths result from Europe's policy of exclusion and closure, those employing a deterrence-oriented narrative have argued for even stricter border controls. Perhaps because of its contentious nature, the debate is often devoid of systematic information on the drivers and dynamics of border deaths. This study contributes to our understanding of border deaths in the Mediterranean region in three ways: it describes and evaluates recent data sources on migration and mortality; it provides a descriptive statistical analysis of absolute and relative mortality risks between 2010 and 2016; and it assesses the relationship between European border policy and border deaths. Our findings challenge the dominant deterrence-oriented policy narrative and highlight the failure of European authorities to address the ongoing humanitarian crisis.